Report on industrial attachment with Merrill Lynch International Bank (Global Wealth Management Technology Asia Pacific.) - He, Lu. (2010)
The main objective of this report is to give a detailed summary of the 22-week Industrial Attachment Program with Global Wealth Management Technology (GWMT) Department of Merrill Lynch Bank of America. The job scope of my project includes software development and application support for the needs of Merrill Lynch’s day-to-day operational activities as well as management business. During the period, I have been actively involved in the design and development of two major projects: (1) Investment Proposal Tool (2) Travel Approval System. And I have successfully delivered several high-quality application releases on time. Each stage of software development life cycle (SDLC) that I have gone through in my projects, from requirements gathering to analysis, coding, UAT and migration, are described in the report. In the meanwhile, the fulfilling and enriching working and life experiences in Merrill Lynch are also mentioned in the report. I feel that it is a great opportunity to hone the technology proficiency as well as business skills here in Merrill Lynch. What I have gained will definitely benefit me forever.